Hidden bedside rationing in the Netherlands: a cross-sectional survey among physicians in internal medicine - Ursula W. de Ruijter; Hester F. Lingsma; Willem A. Bax; Johan Legemaate (BMC, 2021)
Abstract Background Healthcare rationing can be defined as withholding beneficial care for cost reasons. One form in particular, hidden bedside rationing, is problematic because it may result in conflicting loyalties for physicians, unfair inequality among patients and illegitimate distribution of resources. Our aim is to establish whether bedside rationing occurs in the Netherlands, whether it qualifies as hidden and what physician characteristics are associated with its practice. Methods Cross-sectional online questionnaire on knowledge of -, experience with -, and opinion on rationing among physicians in internal medicine within the Dutch healthcare system. Multivariable ordinal logistic regression was used to explore relations between hidden bedside rationing and physician characteristics. Results The survey was distributed among 1139 physicians across 11 hospitals with a response rate of 18% (n = 203). Most participants (n = 129; 64%) had experience prescribing a cheaper course of treatment while a more effective but more expensive alternative was available, suggesting bedside rationing. Subsequently, 32 (24%) participants never disclosed this decision to their patient, qualifying it as hidden. The majority of participants (n = 153; 75%) rarely discussed treatment cost. Employment at an academic hospital was independently associated with more bedside rationing (OR = 17 95%CI 6.1-48). Furthermore, residents were more likely to disclose rationing to their patients than internists (OR = 3.2, 95%CI 2.1-4.7), while salaried physicians were less likely to do so than physicians in private practice (OR = 0.5, 95%CI 0.4-0.8). Conclusion Hidden bedside rationing occurs in the Netherlands: patient choice is on occasion limited with costs as rationale and this is not always disclosed. To what extent distribution of healthcare should include bedside rationing in the Netherlands, or any other country, remains up for debate.